Efficacy versus Toxicity - The Ying and Yang in Translating Nanomedicines. (12th September 2014) - Shankarappa, Sahadev A; Koyakutty, Manzoor; Nair, Shantikumar V
Nanomedicine, as a relatively new offshoot of nanotechnology, has presented vast opportunities in biomedical research for developing novel strategies to treat diseases. In the past decade, there has been a significant increase in in vitro and preclinical studies addressing the benefits of nanomedicines. In this commentary, we focus specifically on the efficacy- and toxicity-related translational challenges of nanocarrier-mediated systems, and briefly discuss possible strategies for addressing such issues at in vitro and preclinical stages. We address questions related specifically to the balance between toxicity and efficacy, a balance that is expected to be substantially different for nanomedicines compared to that for a free drug. Using case studies, we propose a ratiometric assessment tool to quantify the overall benefit of nanomedicine as compared to free drugs in terms of efficacy and toxicity. The overall goal of this commentary is to emphasize the strategies that promote the translation of nanomedicines, especially by learning lessons from previous translational failures of other drugs and devices, and to apply these lessons to critically assess data at the basic stages of nanomedicinal research.